Obesity and Prognostic Variables in Colombian Breast Cancer Patients: A Cross-Sectional Study - Javier Cuello-López; Ana Fidalgo-Zapata; Elsa Vásquez-Trespalacios (International Journal of Breast Cancer)
Introduction. Obesity is an established risk factor for cancer and cancer-related deaths, including that of the breast. While the prevalence of female obesity has accelerated over the past decade in many developing countries, such as Colombia, the prevalence of overweight and obesity specifically in breast cancer populations has not been fully described. Methods. A cross-sectional study including 849 women diagnosed with breast cancer between 2009 and 2014. Based on body mass index, prevalence of overweight (BMI ≥ 25 < 30) and obesity (BMI ≥ 30) and associations of BMI with clinical and tumor histopathological features were analyzed. Results. Colombian breast cancer patients had a prevalence of overweight of 34.28% and obesity of 28.15%. Mean BMI was comparable between premenopausal and postmenopausal women (27.2 versus 27.7, resp.). Among premenopausal women, higher BMI was significantly positively associated with hormone receptor negative tumors, as well as with greater lymphovascular invasion. Conclusions. Colombian breast cancer patients exhibit a significant prevalence of overweight and obesity. Associations of high BMI and poor prognosis variables in the premenopausal population suggest risk of aggressive disease in this population. Future studies to further validate our observations are warranted in order to implement multidisciplinary clinical guidelines.